Self-regulated Learning Model Affects Students’ Mathematical Conceptual Understanding and Self-confidence in terms of Cognitive Styles - Mahayani, N. P. L.; Astawa, I. W.; Suharta, I. G. P. (LPPM Undiksha, 2021)
The main problem in mathematics learning is to form students’ understanding and self confidence. The aim of this study is to analyze the impact of self-regulated learning model on conceptual understanding and self-confidence in terms of cognitive styles. This study was a quasi-experimental study which applies treatment by level design, where the treatment is learning model for students with different cognitive style level. The samples of the study are 80 students in four classes, who are selected using cluster random sampling technique. Data on conceptual understanding are collected by using conceptual understanding test in the form of essay test. While the data on the students’ self-confidence are collected using questionnaires. The data collected are anayzed using manova. The results of the study indicate that self-regulated learning has positive impact on the students’ conceptual understanding and self-confidence (F = 8,796; p < 0,05). Thus, it could be concluded that learning model and cognitive style give significant impact on the students’ conceptual understanding and self-confidence in terms of cognitive styles.